JAMBU_CHAT: An Online Chat Application for Android Smartphone - Tan, Yit Jun; Sapiee Jamel , (Applied Information Technology And Computer Science, 2021)
Nowadays, people often use a chat application to communicate with each other. Different attack can happen on the chat application for example eavesdropping, Man-in-The-Middle attack, and impersonation attack. Authenticated encryption is an algorithm that combines the encryption scheme and message authenticated code. It can ensure message confidentiality and authenticity at the same time. AES JAMBU is an authenticated encryption algorithm that participate the third-round candidate in Competition for Authenticated Encryption: Security, Applicability, and Robustness (CAESAR). AES JAMBU is suitable to apply on lightweight application, so it is suitable to implement on an android chat application. The chat application has been successfully implemented and tested using Android Studio in the JAVA programming language. The database that used in the chat application is the Firebase NoSQL database.